ChemInform Abstract: 4‐Hydroxy‐2‐quinolones. Part 204. Synthesis, Bromination, and Analgetic Properties of 1‐Allyl‐4‐hydroxy‐6, 7‐dimethoxy‐2‐oxo‐1, 2‐dihydroquinoline‐3‐carboxylic Acid Arylalkylamides. Issue 17 (4th April 2013) - Ukrainets, I. V.; Mospanova, E. V.; Jaradat, N. A.; Bevz, O. V.; Turov, A. V.
Abstract A simple method for the synthesis of the title amides (III) (21 examples) is given.